From Hen House to Bedside: Tracing Hanafusa’s Legacy from Avian Leukemia Viruses to SRC to ABL and Beyond - Kharas, Michael G. (SAGE Publications, 2010)
The discovery of the Src oncogene was the first step on a long journey toward improved cancer chemotherapy. In this review, we explore Src and BCR-ABL, signal transduction, and recent advances in oncogene addiction and celebrate Hidesaboro Hanafusa and the many researchers who ushered in the age of target-directed therapy against tyrosine kinase oncoproteins.